Critérios de delimitação de áreas de influência em Estudos de Impacto Ambiental de rodovias: abordagem de processos de dinâmica superficial - Menin, Fernanda Asseff [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; Do Carmo Giordano, Lucilia [UNESP]; Do Amaral, Ana Maria Carrascosa [UNESP]; Gabelini, Beatriz Marques [UNESP]; Cerri, Rodrigo Irineu [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
The aim of this paper is to evaluate the geographic boundaries (influenced and study areas) delimitation criteria on highways Environmental Impact Studies (EIS), focusing on the physic environment associated with dynamic surficial process. Means to achieve, it was analyzed four environmental licenses proceedings of Tamoios' highway, located in north coast of São Paulo State in Brazil. Outcomes show that this split of the environmental licenses proceedings into four EIS in a short time does not enable the whole feasibility assessment, including the geographic boundaries delimitation. There was not a discussion about the criteria used to define these areas, so it is not possible to understand the proposed limits, especially because they are land bands nearby the linear construction. In addition, the limitation did not examine physic and biotic environment and socioeconomic components. As a suggestion, the delimitation criteria of the closest geographic boundaries (ADA) must use dynamic surficial process information and geomorphologic, geology, pedology and geotechnics components. Likewise, the proposal is to restrict the larger geographic boundaries to watershed limits for linear projects. Another important topic is to discuss the delimitation issue during the EIS scope, just before the environmental license begin.
Geographic boundaries delimitation proposal for highways Environmental Impact Studies: Approaching dynamic surficial process
Keywords: Dynamic surficial process; Geographic boundaries; Highways; Physical environment